Elective First-Line Use of Dimethyl Fumarate in Psoriasis: Insights from an Italian Cohort - Giunta, Alessandro; Esposito, Maria; Campione, Elena; Burlando, Martina; Caldarola, Giacomo; Lora, Viviana; Diotallevi, Federico; Tolino, Ersilia; Silvi, Gianmarco; Cozzani, Emanuele; Shumak, Ruslana Gaeta; Fidanza, Rosaria; et al. (Dermatology Practical & Conceptual, 2025)
Introduction: Dimethyl fumarate (DMF) is an approved conventional systemic treatment for psoriasis that does not exhibit any drug–drug interactions or cumulative organ toxicities.Aim: This retrospective real-world study aimed to analyze the long-term efficacy, safety, and tolerability of DMF in patients with moderate psoriasis.Methods: Data on safety and efficacy were collected from medical charts. The effect on disease severity was assessed using the Psoriasis Area Severity Index.Results: Our study included 148 patients over a 48-week treatment period, confirming DMF as an effective option in the treatment of moderate psoriasis. Adverse events were only mild or moderate, principally flushing, epigastralgia, and diarrhea. However, DMF exhibited a delayed onset of action, and the dropout rate was high. These aspects highlight the importance of educating patients about the activity profile of DMF, the potential occurrence of side effects, and their management. However, side effects are self-limiting with discontinuation of treatment and generally occur early, allowing patients to be promptly switched to other therapies if DMF is not tolerated.Conclusions: Our results confirm that DMF may be offered as a first-line treatment for moderate psoriasis as it demonstrated efficacy even in the long-term, when treatment is tolerated, especially in patients with a disease duration of less than five years. DMF may also be proposed when the patient presents comorbidities, when immunosuppression is undesired, and/or before the initiation of biological therapies.